Analisis faktor-faktor yang mempengaruhi motivasi kerja pada generasi milenial di Cipta Grafika - Widiastuti, Imelda Amelia; Isyanto, Puji (Relawan Sosial Ekonomi (RSE) Publisher, 2024)
The millennial generation plays an important role in changing the dynamics of the current labor market, especially in the creative and information technology sectors such as those faced by Cipta Grafika. This study aims to identify the main factors that influence the work motivation of the millennial generation at Cipta Grafika. The research method used is qualitative analysis with a descriptive approach, involving data collection through in-depth interviews and focused observation of millennial generation employees in various company departments and Cipta Grafika. The research results show that factors such as work flexibility, recognition of contributions, opportunities for career development, and a supportive work environment significantly influence the level of work motivation of the millennial generation at Cipta Grafika.